Komunikasi Krisis Kebijakan Karantina Hotel Terhadap Citra Pariwisata - Purwantoro, Tono; Sukirno, Zakaria Lantang (Journal of Tourism and Creativity, 2023)
The impact of Covid-19 in Indonesia has not ended until November 28 2022 there is 36,057 people were exposed and 4,516,480 people were confirmed since the first Covid-19 declare. The government's anticipation during the January 2022 pandemic closed entry for arrivals from various countries through policy number 14 dated 13 October 2021 and No. 1 of 2022 concerning the behavior of entry points, quarantine places and RT-PCR obligations for Indonesian citizens traveling abroad for 10-14 days. International travelers, according to the Decree, are required to quarantine 5 x 24 hours for those who have been vaccinated and 14 x 24 hours from countries with a high escalation of positive cases. The policy was updated January 1 2022 for a 12x24 hour quarantine period, changing February 2022 to have an impact on the tourism industry, especially hospitality. The hotel quarantine policy drew criticism after the Task Force issued a list of 66 hotels. Efforts to revive the hospitality industry through political economy. Public policy is the answer to the problem. Often policies conveyed through government communications foster crisis communication as a result of the contents of the message being conveyed there are irregularities. Crisis communication occurs when negative news about the difficulty and lengthy time of getting hotel quarantine colors the media pages.